Intraneural nodular fasciitis in peripheral nerves: report of two cases and literature review - Yeting Wang; Wen Chen; Tiezheng Wang; Kezhen Qin; Jianbo Teng; Hengtao Qi (BMC Musculoskeletal Disorders)
Abstract Background Although nodular fasciimmon and can occur in various anatomical locations, its occurrence within a nerve is extremely rare. Nodular fasciitis usually resolves spontaneously after partial resection. However, it often presents diagnostic challenges due to its resemblance to malignant diseases, resulting in excessive treatments such as extended nerve excision and nerve transplantation. Case presentation We report two cases of intraneural nodular fasciitis. A 37-year-old woman presented with left upper limb numbness and pain, without trauma history. Preoperative ultrasound was performed. Subtotal resection of the mass in the superficial branch of the radial nerve was conducted. Postoperative pathology and immunohistochemistry confirmed intraneural nodular fasciitis. At 9-month follow-up, symptoms resolved with no recurrence of the mass. A 15-year-old female presented with progressive right lower limb numbness, later accompanied by pain, distal muscle weakness, and difficulty in lifting the foot. Preoperative ultrasound and magnetic resonance imaging were performed. The mass within the sciatic nerve was completely removed. Postoperative pathology and immunohistochemistry confirmed intraneural nodular fasciitis. At 3-month follow-up, symptoms resolved with no recurrence of the mass. Conclusions Accurate diagnosis of intraneural nodular fasciitis is crucial to prevent unnecessary treatment. Its ultrasound and magnetic resonance imaging features lack specificity. Preoperative biopsy using ultrasound or computed tomography guidance may be considered if necessary and safe. The histopathological features for intraneural nodular fasciitis exhibits spindle cells in a tissue-culture-like pattern within a richly myxoid matrix, abundant capillaries, inflammatory cell infiltration, frequent mitotic figures without atypia, and infiltrative margins. Immunohistochemically, intraneural nodular fasciitis is characterized by SMA(+) and S100(-). Surgical excision of the lesion is necessary to prevent neurological deficits. And the vast majority of intraneural nodular fasciitis cases spontaneously regress after subtotal resection. A comprehensive diagnostic approach is recommended when intraneural nodular fasciitis is suspected. This article analyzes the diagnostic workup and pathogenesis of all 13 reported intraneural nodular fasciitis cases (including our two), aiming to aid clinicians in achieving precise diagnosis and avoiding overtreatment.